2010
DOI: 10.1002/chem.201000216
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical and Nonsymmetrical Chromophores with Tröger’s Base Skeleton: Chiroptical, Linear, and Quadratic Nonlinear Optical Properties—A Joint Theoretical and Experimental Study

Abstract: We report on the novel chiral push-pull chromophores derived from 6H,12H-5,11-methanodibenzo[b,f][1,5]diazocine (Tröger's base skeleton). The synthesis of symmetrical chromophores featuring two identical acceptors, as well as the synthesis of unsymmetrical chromophores featuring only one acceptor is given. Symmetrical chromophores were prepared in the enantiomerically pure form and their chiroptical properties were investigated. Second-order nonlinear optical (NLO) properties of new chromophores were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 81 publications
(100 reference statements)
2
29
0
Order By: Relevance
“…To resolve racemic TB 2 we employed HPLC column Reprosil Chiral NR; an equivalent of Whelk O1, which is efficient for resolving various TB derivatives . We reached separation selectivity 1.16, and resolution 0.83.…”
Section: Resultsmentioning
confidence: 98%
“…To resolve racemic TB 2 we employed HPLC column Reprosil Chiral NR; an equivalent of Whelk O1, which is efficient for resolving various TB derivatives . We reached separation selectivity 1.16, and resolution 0.83.…”
Section: Resultsmentioning
confidence: 98%
“…For example, Sergeyev's group reported the synthesis and optical properties of bi-chromophoric systems with two para-nitrophenyl or benzothiazolium acceptors, i.e., of 4 and 5 ( Figure 11) [50]. The results indicated that the combination of donor--acceptor design and the inherent chirality of the molecule hold considerable promise as a scaffold for nonlinear optics (NLO) chromophores.…”
Section: Other Optoelectronic Examples Of Tb Analoguesmentioning
confidence: 99%
“…Organic light‐emitting diodes (OLEDs) fabricated with these TB analogues show high brightness, high efficiency, and low turn‐on voltage. Benzothiazolium‐ and para ‐nitrophenyl‐derived TB analogues 114 and 115 , respectively (Figure 33), show second‐order nonlinear optic properties, the former being the more active 89,124…”
Section: Other Applications Of Tröger's Basementioning
confidence: 99%